On the short-time thermal phase-stability of as-cast AlCoCrFeNi2.1 eutectic high entropy alloy - J. Charkhchian; A. Zarei-Hanzaki; A. Moshiri; H.R. Abedi; Jiajia Shen; J.P. Oliveira; Kanwal Chadha; Clodualdo Aranas, Jr. (Journal of Materials Research and Technology, 2022)
The present work deals with the short-time thermal phase-stability of the as-cast eutectic AlCoCrFeNi2.1 high entropy alloy. Toward this end, the effect of different temperatures (800–1000 °C) and soaking times (15–60 min) on the stability of primary dendritic regions and formation of the ordered phases was explored. Microstructural characterization was supported by thermodynamic calculations and assessment of the subsequent mechanical properties. Upon the increase in annealing temperature and soaking time, the primary FCC dendritic areas grown and destabilized owing to elemental partitioning. This was followed by dendrite fragmentation and formation of needle shape B2 ordered phases within the primary FCC regions. Despite the unstable nature of the primary constituent phases, the material hardness increased considerably to a peak point corresponding to the moderate soaking time of 45 min. The variation of the subsequent mechanical properties was discussed relying on the characteristics of the ordered and primary phases.